Consuming people : from political economy to theaters of consumption - Firat, A. Fuat; Dholakia, Nikhilesh, 1947- (London ; New York : Routledge, 1998)
Looks at people in the act of consumption and consumed by the act of consumption, combining academic analysis with a discussion of the possibilities for consuming people in the future. Previously only available in hardback.
The Consuming Society 2. Consumption Patterns 3. Making of the Consumer 4. Consumption in Modern Society 5. The Social Construction of Consumption Patterns in Modern Society 6. (Post)Modernity and Consumption 7. Postmodern Consumption 8. Global Consumption 9. Consuming People 10. The New Theater of Consumption
Includes bibliographical references (p. [161]-188) and index
Keywords: Consumption (Economics) -- History